2011
DOI: 10.2108/zsj.28.659
|View full text |Cite
|
Sign up to set email alerts
|

Male Aggressive Behavior and Exaggerated Hindlegs of the Bean BugRiptortus pedestris

Abstract: Males of the bean bug species Riptortus pedestris possess larger hindlegs than females. Observations of male-male interactions showed that the enlarged hindlegs are used as weapons in male fights, and that males with larger hindlegs win fights more frequently. Morphological analysis based on the positive allometry test showed that the femora of larger males are relatively bigger than those of smaller males, but femora of larger females are not relatively larger than those of smaller females. These results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 31 publications
0
31
2
Order By: Relevance
“…1). Weapon size is positively associated with competitive ability for mates [42], [43]. In this species, males establish their territories on soybean plants [41] and call over conspecific individuals irrespective of sexes by aggregation pheromone [72].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Weapon size is positively associated with competitive ability for mates [42], [43]. In this species, males establish their territories on soybean plants [41] and call over conspecific individuals irrespective of sexes by aggregation pheromone [72].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, adults did not interact with conspecifics until the following experiments. For a more detailed description of the stock culture, see Okada et al [42]. We performed all rearing and experiments in a chamber maintained at 25°C, 60% relative humidity and with a photoperiod cycle of 16∶8 h light∶dark.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allometric growth has been studied extensively in fish and crustaceans (e.g., Aldrich 1974;Huber 1985;Aritaki et al 2000Aritaki et al , 2003, and several studies have found that allometric growth is closely linked to ontogenetic changes in behavior (Zelditch and Fink 1995;Gisbert 1999;Kobayashi 2002;Choo and Liew 2006). In insects, there have been considerable studies on static allometry (see Klingenberg and Zimmermann 1992;Stern and Emlen 1999) for body structures such as the horns of male beetles (Emlen and Nijhout 1999) and the legs of adult true bugs (Eberhard 1998;Okada et al 2011). Few studies, however, have addressed the correlation between ontogenetic allometry for body structures against body size and ontogenetic changes in behavior in insects (but see Koshikawa et al 2002;.…”
Section: Introductionmentioning
confidence: 99%